Mutating Neoliberalism: The Promotion of Italian Investors in Slovakia before and after the Global Financial Crisis - Sellar, Christian; Pástor, Rudolf (International Journal of Urban & Regional Research, 2015)
In the context of the literature on 'actually existing neoliberalisms', this article analyzes the policies and services supporting Italian foreign direct investment (FDI) in Slovakia. It identifies a group of organizations, both Slovak and Italian, which shape and deliver neoliberal pro-FDI policies. By studying such an 'investment promotion community' (IPC) before and after the global financial crisis of 2009, and during Italy's prolonged crisis, this article shows both the persistence and adaptability of neoliberal policies and institutions. In so doing, it highlights some of the transnational flows underpinning the 'domestication' of neoliberalism in Slovakia. These findings support recent literature arguing that post-crisis neoliberalism can be interpreted as a stunted Polanyian double movement, in which the state has improved some of its regulatory functions but without questioning the overarching neoliberal principles. Specifically, it shows that FDI policies and the support of Italian investors rest upon a professional community that has not changed much since the 2009 crisis. This community played a crucial role in embedding neoliberal rationalities in Slovakia and supports the persistence of this ideology in the post-crisis environment.
Political Science; Public Administration
Keywords: Bratislava; Italy; Košice; Kralovsky Chlmec; Slovakia; Slovakia - economic conditions; Slovakia - foreign economic relations; capitalists & financiers; double movement; financial crisis; foreign direct investment; foreign investments; global financial crisis; 2008-2009; neoliberalism